Comparative Genomics Of Β- Subunit Of Tryptophan Synthase Among A Group Of Proteobacteria - SATPAL SINGH BISHT; SANTOSH KUMAR BEHERA; AMRITA PANDA; B.PRAVEEN. (International Journal of Pharma and Bio Sciences, 2011)
Proteins are macromolecules with a characteristic sequence of amino acid linked by peptide bond and play a vital role in metabolic pathways. There are 20 major amino acids and hundreds of "minor amino acids" - some are short-lived and some are the modifications of the main 20. Tryptophan synthase, in the biosynthetic pathway of the aromatic amino acid Tryptophan is regulated by the “trp operon” in E.coli. Tryptophan: In the Shikimic acid pathway, Chorismate is a key intermediate in the biosynthesis leading to the formation of the aromatic amino acids (phenylalanine, tyrosine and tryptophan). Tryptophan Synthase is a bifunctional, bienzyme complex having two α chains and two β chains that forms the a2b2 tetrameric enzyme complex. In most of the organisms α chain is encoded by the gene trpA and β chain is encoded by the gene trpB. Salmonella typhimurium was taken as a reference organism for comparative genomics of Tryptophan synthase and data that was available for comparative genomics was interrogated with bioinformatics tools. The amino acid (aa) sequence of tryptophan synthase beta chain of Salmonella typhimurium from the PDB was taken as the standard sequence and pair-wise alignments and multiple sequence alignment was pursued for all the 41 proteobacteria using BLAST 2 programme and Clustal X (1.83). phylogenitic analysis was drawn by using tree view.